2023
DOI: 10.3390/foods12163126
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Quality Analysis of Different Colors of Medicinal and Edible Honeysuckle

Zhenying Liu,
Yunxia Cheng,
Zhimao Chao

Abstract: Honeysuckle (the dried flower bud or opening flower of Lonicera japonica Thunb.), a medicinal and edible substance, has is greatly popular among consumers for its remarkable health effects, such as antioxidant, antibacterial, and anti-inflammatory effects. However, due to the influences of processing methods, storage conditions, and other factors, honeysuckles show different colors which can directly reflect the quality and the price on the market. In order to comprehensively compare the quality of different c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Specific flavonoids like luteolin, quercetin, isoquercetin, and rutin have been recognized for their potent antibacterial, anti-inflammatory, antioxidant, and antitumor properties, which are fundamental to the therapeutic efficacy of medicinal plants ( Seelinger et al., 2008 ; Naveed et al., 2018 ; Zwicker et al., 2019 ; Yang et al., 2020 ; Zheng et al., 2024 ). Chlorogenic acid and luteolin, in particular, are abundant in honeysuckle and have garnered extensive pharmacological interest due to their efficacy as medicinal components ( Wang, 2017 ; Liu et al., 2023 ). Chlorogenic acid, alongside total flavonoid content, is also employed as a quality control benchmark in honeysuckle, as evidenced by the 2020 Chinese Pharmacopoeia, which mandates a minimum content of 1.5% ( Zheng et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Specific flavonoids like luteolin, quercetin, isoquercetin, and rutin have been recognized for their potent antibacterial, anti-inflammatory, antioxidant, and antitumor properties, which are fundamental to the therapeutic efficacy of medicinal plants ( Seelinger et al., 2008 ; Naveed et al., 2018 ; Zwicker et al., 2019 ; Yang et al., 2020 ; Zheng et al., 2024 ). Chlorogenic acid and luteolin, in particular, are abundant in honeysuckle and have garnered extensive pharmacological interest due to their efficacy as medicinal components ( Wang, 2017 ; Liu et al., 2023 ). Chlorogenic acid, alongside total flavonoid content, is also employed as a quality control benchmark in honeysuckle, as evidenced by the 2020 Chinese Pharmacopoeia, which mandates a minimum content of 1.5% ( Zheng et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cynaroside (Cy) is the 7-O-glucoside of luteolin, a avone (subclass of avonoids) naturally occurring in several plant species, including Lonicera caerulea L. (honeysuckle) (Bouyahya et al 2023). Several studies have reported that Cy has numerous pharmacological properties, such as antibacterial, antifungal, antileishmanial, antioxidant, hepatoprotective, antidiabetic, anti-in ammatory, and anticancer properties (Bouyahya et al 2023;He et al 2023;Liu et al 2023). Although Cy has good biological activity, its application is limited due to its low extraction e ciency and high cost.…”
Section: Introductionmentioning
confidence: 99%